Polydopamine–polyethylene glycol–albumin antifouling coatings on multiple substrates. Issue 6 (24th January 2018) - Goh, S. C.; Luan, Y.; Wang, X.; Du, H.; Chau, C.; Schellhorn, H. E.; Brash, J. L.; Chen, H.; Fang, Q.
Abstract : Polydopamine–PEG coatings on different substrates: effects of PDA layer properties on PEG grafting and anti-biofouling properties. Abstract : Aqueous-based coatings using combinations of polydopamine (PDA) (as bioadhesive) and grafted polyethylene glycol (PEG) (as antifouling agent) have been reported to reduce biofouling on multiple material surfaces. However, the achievable PEG grafting density and antifouling performance are limited, leaving exposed PDA to provide sites for attachment of proteins and cells. In the present work, we investigate the polymerization of dopamine on three substrate materials, polycarbonate membrane (PC), polydimethyl siloxane (PDMS), and soda lime glass, to evaluate the utility of the PDA coatings for application to multiple materials. Additionally, we propose that the PDA–PEG method may be improved by "backfilling" with bovine serum albumin (BSA) as a blocker covering exposed PDA. AFM and ellipsometry studies revealed substantial differences in PDA thickness and roughness on each material despite their being modified under the same conditions. X-ray photoelectron spectroscopy (XPS) and water contact angle data revealed differences in PEG grafting on these materials as a consequence of varying PDA surface roughness, with the highest PEG coverage achieved on PC–PDA surfaces of intermediate roughness and lower PEG attachment on smoother PDMS–PDA surfaces. Fibrinogen adsorption experiments showed significantly less fouling on PDA–BSA surfaces compared to PDA–PEG for all three substrates, the larger BSA molecules presumably providing greater coverage of the PDA. On the PC and PDMS substrates, backfilling the PDA–PEG surfaces with BSA gave significant reductions in fibrinogen adsorption, with the lowest adsorption of 75 ng cm −2 achieved on PC–PDA–PEG/BSA.